2023
DOI: 10.1111/joa.13959
|View full text |Cite
|
Sign up to set email alerts
|

Morphological features of the greater occipital nerve and its possible importance for interventional procedures

Latif Saglam,
Ozcan Gayretli,
Osman Coskun
et al.

Abstract: Being one of the most prevalent neurological symptoms, headaches are burdensome and costly. Blocks and decompression surgeries of the greater occipital nerve (GON) have been frequently used for migraine, cervicogenic headache, and occipital neuralgia which are classified under headache by International Headache Society. Knowledge of complex anatomy of GON is crucial for its decompression surgery and block. This study was performed to elucidate anatomical features of this nerve in detail. Forty‐one cadavers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…There was a statistical significance between genders for the perpendicular distance of the LON to the vertical line passing from the EOP ( p = 0.027). Saglam et al obtained a similar result for the GON and reported that this may be due to the differentiation of the nerve for the genders during embryologic development 20 . We think that the statistical difference we obtained may be due to similar reasons.…”
Section: Discussionmentioning
confidence: 62%
“…There was a statistical significance between genders for the perpendicular distance of the LON to the vertical line passing from the EOP ( p = 0.027). Saglam et al obtained a similar result for the GON and reported that this may be due to the differentiation of the nerve for the genders during embryologic development 20 . We think that the statistical difference we obtained may be due to similar reasons.…”
Section: Discussionmentioning
confidence: 62%
“…There was a statistical signi cance between genders for the perpendicular distance of the LON to the vertical line passing from the EOP (p = 0.027). Saglam et al obtained a similar result for the GON and reported that this may be due to the differentiation of the nerve for the genders during embryologic development 20 . We think that the statistical difference we obtained may be due to similar reasons.…”
Section: Morphometric Featuresmentioning
confidence: 62%
“…In cadaveric studies, the relationship between the GON and OA appears intricate, as they might run in a parallel fashion at certain junctures and intersect at others. In a study involving 73 cadavers, the GON and OA had crossed once in 78% of cases, twice in 7%, and three times in 4% 55 . Additional research is needed to investigate whether interactions between the OA and the GON are associated with symptomatic improvement following surgery.…”
Section: Discussionmentioning
confidence: 98%